Transboundary water governance challenges in the Mahakali River basin: a view from Nepal and way forward - Tiwari, K.; Pant, R. R.; Shah, D. N. (Informa UK Limited, 2025)
The Mahakali River, a key tributary of the Ganges, is shared by Nepal and India. The 1996 Mahakali Treaty aimed to promote cooperation, but after almost three decades, effective transboundary governance has remained limited. This study examines governance attributes like rule of law, transparency, accountability and inclusiveness through interviews, legal reviews, and secondary sources. It identifies inadequate implementation of these principles, influenced by politically driven, nation-centred approaches. The study critiques the treaty’s inequities and proposes a collaborative basin water policy framework. These findings provide insights for improving water governance and sustaining the Mahakali and other transboundary rivers.